Pengaruh Etos Kerja Dan Kepuasan Kerja Terhadap Kinerja Pegawai Pada Suku Dinas Pendidikan Wilayah II Kota Administrasi Jakarta Selatan - M. Gilang Pratama; Adi Nugroho (JURNAL MANAJEMEN PENDIDIKAN, 2026)
The Influence of Work Ethic and Job Satisfaction on Employee Performance in the Education Office Region II of the South Jakarta Administrative City This study aims to analyze the influence of work ethic and job satisfaction on employee performance at the Regional Education Office II of South Jakarta Administrative City. This research employed a quantitative method with a causal associative approach. The population consisted of 100 employees, and 80 respondents were selected as samples using the Slovin formula. Data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination analysis with the assistance of SPSS version 26. The results indicate that work ethic has a positive and significant effect on employee performance. Job satisfaction also has a positive and significant effect on employee performance. Simultaneously, work ethic and job satisfaction have a positive and significant effect on employee performance at the Regional Education Office II of South Jakarta Administrative City. The coefficient of determination (R²) value of 0.567 indicates that work ethic and job satisfaction explain 56,.7% of the variation in employee performance, while the remaining 43.3% is influenced by other factors not examined in this study.